2016
DOI: 10.1159/000452252
|View full text |Cite
|
Sign up to set email alerts
|

Association between Recreational Physical Activity and the Risk of Upper Urinary Calculi

Abstract: Objective: Upper urinary calculi (UUC) is considered to be a comprehensive disease associated with many risk factors, but the role of physical activity (PA) is undefined. Here, we conducted a cross-sectional study to investigate this relationship in Asian populations. Materials and Methods: Patients diagnosed with UUC were the subjects of study and those who participated in a health examination in local medical center were included as controls. Information was collected through the same standard questionnaire.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Niroomand, et al 21 and Azimi's, et al 10 reported that the majority of kidney stones patients had a low level of physical activity or even did not exercise at all. This was further reinforced by Chen, et al 13 highlighting that healthy people had higher physical activity levels compared to those with kidney stones. Fagagnini, et al 14 also stated that physical activity per day or week was associated with a lower risk compared to per month.…”
Section: Disscusionmentioning
confidence: 85%
See 2 more Smart Citations
“…Niroomand, et al 21 and Azimi's, et al 10 reported that the majority of kidney stones patients had a low level of physical activity or even did not exercise at all. This was further reinforced by Chen, et al 13 highlighting that healthy people had higher physical activity levels compared to those with kidney stones. Fagagnini, et al 14 also stated that physical activity per day or week was associated with a lower risk compared to per month.…”
Section: Disscusionmentioning
confidence: 85%
“…Lack of physical activity increased the risk of developing kidney stones through exacerbation of hypercalciuria 14,18 . Meanwhile, adequate and regular-mild to moderate physical activity reduced the risk by lowering calcium excretion in the urine 10,13,14,21 . Excessive physical activity may also increase the occurrence of kidney stones when not balanced with fluid adequate intake to compensate for the sweat loss 14,15,23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moderate physical activities can help dislodge small calculi and facilitate their expulsion, while excessive physical activities lead to significant fluid loss, concentration of blood, and reduced urine discharge. [ 7 ] Consequently, individuals with physically demanding workloads are more susceptible to urinary system calculi.…”
Section: Discussionmentioning
confidence: 99%